Role of termites in the restoration of soils and plant richness on bowé in West Africa. - Padonou, Elie; DJAGOUN, CHABI A.M.S.; Akakpo, Alexis; Ahlinvi, Simon; Lykke, Anne M.; Schmidt, Marco; ASSOGBADJO, ACHILLE EPHREM; SINSIN, AUGUSTIN BRICE (My University, 2020)
Bowé (hardened ferricrete soils formed by erosion, drought or deforestation) are often associated with termite mounds, but little is known about these mounds and their role in the restoration of soils and plant biodiversity on bowé. This study ex-amined termite mounds on bowé and their effects on soil depth and plant richness. Sixty-four sampling plots were laid out randomly on bowé sites with mounds and on adjacent bowé sites without mounds. The height and circumference of each mound were measured. Species inventories were made and soil depth measured in each plot. Linear mixed effects and generalised mixed effects models with Poisson error dis-tribution were used to assess the variation in soil depth and plant species richness in mound and nonmound microsites. Two types of mounds (small vs. large) associ-ated with different termite species were observed on bowé, with the small mounds being most common. Plots with either large or small mounds had deeper soils and higher plant richness than the adjacent plots without mounds. Conservation of ter-mite mounds is important for restoring soils and plant richness on bowé, and ter-mite mounds should be taken into consideration in biodiversity and soil management strategies for bowé.
Keywords: Benin; bowé; plant diversity; soil restoration; termite mounds; West Africa